Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D; Büker, Patrick; Ashmore, Mike R (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D.; Büker, Patrick; Ashmore, Mike R. (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
The following values have no corresponding Zotero field: accession-num: 17412465
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
Keywords: stomata; taxonomy; Trichomes; waxes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: stomata; taxonomy; Trichomes; waxes

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M. M.; Pereira, J. S.; Cerasoli, S.; CliftonBrown, J.; Miglietta, F.; Raschi, A.; Chaves J. S. ;Cerasoli, S. ;Clifton Brown (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)The following values have no corresponding Zotero field: pub-location: OSNEY MEAD, OXFORD, OXON, ENGLAND OX2 0EL publisher: BLACKWELL SCIENCE LTD label: Fisiologia - CO2 elevado
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A; Chaves J. S.;Cerasoli,S.;Clifton Brown,J.;Miglietta,F.;Raschi,A., M M ;Pereira (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits

The stomata of the cork-oak, Quercus suber. An ultrastructural approach - Molinas, M L (Nordic Journal of Botany, 1991)
In the evergreen leaves of Quercus suber, stomata play a major role in adaptation to drought and temperature stress. The leaf is of zygostomic type and has about 430 stomata per square milimeter of abaxial leaf surface. The stomatal complex is of the anomocytic type. The guard cells protrude from the epidermal plane. The guard cell nucleus contains heterochromatin in small granules. The guard cell cytoplasm is characterised by a large number of well developed mitochondria, amyloplasts with stroma and grana, and a well developed cytoskeleton with a cortical array of microtubules oriented pa railed to the slit axis that persist even in mature cells. Guard cell walls are asymmetrically thickened and devoid of plasmodesmata. No area of cell walls was free of cuticle or covered by a thin cuticular layer and apparently no area of limited cuticular development provides evaporation when the stomata are closed.
Keywords: Quercus suber; stomata; ultrastructure (PG)